Aplikasi Jenis Pupuk Organik pada Tanaman Padi Sistem Pertanian Organik - I NYOMAN YOGI SUPARTHA; GEDE WIJANA; GEDE MENAKA ADNYANA (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2012)
ABSTRACT Application Types of Organic Fertilizer for Rice (Oryza sativa L.) in Organic Farming Systems Rice plants (Oryza sativa L.) is a plant food as an energy source that is generally consumed by the people of Indonesia. Nearly half the world's population, especially in Asia dependent of the rice plant. Once the importance of rice that could lead to crop failures widespread social unrest. One of the efforts to increase the productivity of rice plants is to replenish nutrient needs through fertilization. This experiment aims to find the best combination between solid organic fertilizer with liquid organic fertilizer on the growth and yield of rice plants. The results showed that the combination treatment of solid organic fertilizer and liquid organic fertilizer does not significantly affect plant growth variables, but the real influence the outcome of the rice plant. The addition of liquid organic fertilizer in rice planting organic system able to increase the yield of dry grain yields of 4.4% - 17.4%. Results of dry grain harvests and grain yield obtained at the highest oven dry fertilizer additions AA-01 (5.07 tonnes / ha dry grain harvest, and 3.94 tonnes / ha oven dried grain). Suggestions can be thought of, in organic rice farming system suggested combining solid fertilizer with liquid fertilizer, so that the growth and yield can be improved, and the need to study solid organic fertilizers and other liquid organic fertilizer in order to obtain higher yields Keyword: organic fertilizer, growth and yields, organic farming systems